Prevalencia de vida de uso de cannabis y rendimiento académico en adolescentes (2015)
Objective: This research compares and establishes the differences in the prevalence of life (consumption ever in life) and no lifetime prevalence of cannabis use on academic performance in school adolescents. Method: In this descriptive and cross sectional study 156 students were probabilistically selected and evaluated with an ad-hoc auto-perception test. The techniques used were frequency analysis, descriptive, student t, Mann Whitney and Chi2. Results: The results show differences between groups in the prevalence of cannabis use and no prevalence of cannabis in the number of repeated courses, days punished in the past month, the average of the last month note, school problems and concern for these and difficulty controlling behavior in the past six months. There were no differences in the comparison between men and women in the group prevalence of cannabis use. It confirms that cannabis affects academic performance from some specific factors that affect both men and women. Conclusion: It is concluded that the group of lifetime prevalence of cannabis use more repeaters in turn have repeated more courses, have received more punishment in school, they have lower grades, have more problems in school and have been more worried about these, and greater difficulty in controlling behavior, and that there are no gender-related differences in the effects on academic performance after trying cannabis. © 2015, Universidad del Norte. All rights reserved.